Analysis Conextivity Sidewalk Desaign In Tasikmalaya School Area - Yogi Arisandi; Khusnul Khotimah (Syntax Corporation Indonesia, 2020)
In some areas of Tasikmalaya there is an education zone. Conditions in the zone, some students are forced to walk on the road because of the unavailability of sidewalks or dealing with traffic vehicles passing by and very unfriendly to school children. To improve the safety, comfort and safety of pedestrian users, it is necessary to plan the needs of integrated pedestrian facilities in Tasikmalaya Regency. In this study using pedestrian analysis method that is done on sidewalk and pedestrian way and method of alignment analysis. It was found that the volume of vehicles> 1000 vehicles / 12 hours and pedestrian volume> 300orang / 12 hours. Pedestrian facilities such as sidewalks and pedestrian facilities are indispensable in the education zone of Tasikmalaya Regency to minimize conflicts (vehicles and pedestrians). In one of the research sites, namely on Jl. K. H. Zaenal Musthafa requires pelican crossing because of the huge volume of vehicles and the very high volume of pedestrians. Integrated pedestrian concept is done by connecting Jl. Paledang with Jl. Garut-Tasikmalaya, Jl. Bantar Payung- Jl.Garut-Tasikmalaya.